Local stakeholder engagement of mineral exploration companies within the corporate social responsibility (CSR) framework: Insights into companies operating in Northern Finland - Ziessler-Korppi, Sofia (2013)
After the turn of the millennium, criticism towards the global mining industry has awakened mining companies to the need for addressing not only their shareholders but also a wider set of stakeholders as part of their corporate social responsibility (CSR). CSR is not only about ethics, but it entails also business benefits and political power implication, and there is essentially a social demand for it. Companies engaging with their local stakeholders already from the beginning of mineral exploration seem to have better opportunities for building sound company-stakeholder relationships, supporting also the social licence to operate (SLO) in the actual mining stage. In Northern Finland the relevance of the mining industry's local stakeholder engagement has been underlined due to the ambiguous discourses of the need for an inclining economy and nature conservation. The purpose of this study is to look into how mineral exploration companies approach their local stakeholders in this challenging context. The study presents perspectives of three transnational mineral exploration companies on local stakeholder engagement in Northern Finland. The qualitative, empirical data was gathered by 14 semi-structured interviewees with employees from different levels of the three case companies' local business units. The three case companies expressed a high motivation for local stakeholder engagement. The activity was seen as a requisite of the case companies' local operations and a source of business benefits, but it was also internalized as ethical behaviour and corporate citizenship. Bad reputation of the industry in Finland, slow licence processing, volatile price development as well as operating in a sensitive natural environment were some of the case companies' shared challenges to overcome. However, despite the various mutual and company-specific challenges in the local contexts, all three case companies still considered to having succeeded in gaining and maintaining the local stakeholders' trust and approval. Openness, ...